2015
DOI: 10.5415/apallergy.2015.5.4.203
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, practices on allergic rhinitis of generalists and specialists in Philippine National Capital Region

Abstract: BackgroundTreatment of allergic rhinitis (AR) consistent with consensus guidelines is reported to result in better patient outcomes. However, physicians may manage patients independently of guidelines. Asian data on physician perspectives regarding AR diagnosis and management is limited.ObjectiveThe study objective is to assess attitudes and practices on AR of Filipino specialists and generalists.MethodsA cross sectional survey of 100 specialists and 100 generalists was conducted from November 2014 to January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 19 publications
2
9
0
Order By: Relevance
“…In a previous survey, general and specialist physicians in the Philippine NCR perceive cost to be the primary reason for noncompliance of patients with therapeutic regimens. Similarly, the finding of antihistamines as the most commonly used prescription drugs is also consistent with the same survey where antihistamines are reported as the preferred single drug treatment of Filipino physicians for mild or moderate-severe AR [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…In a previous survey, general and specialist physicians in the Philippine NCR perceive cost to be the primary reason for noncompliance of patients with therapeutic regimens. Similarly, the finding of antihistamines as the most commonly used prescription drugs is also consistent with the same survey where antihistamines are reported as the preferred single drug treatment of Filipino physicians for mild or moderate-severe AR [ 22 ].…”
Section: Discussionsupporting
confidence: 85%
“…The survey results demonstrated that antihistamines, particularly 2 nd generation antihistamines, are still the mainstay of AR treatment in primary care practice within Malaysia, Philippines, Thailand and Indonesia. This correlated with a survey from the Philippines [ 11 ] that assessed the specialists’ and GPs’ attitudes and practices followed for the treatment of the AR patients. The authors showed that monotherapy, mainly antihistamines, was the preferred choice for mild AR treatment.…”
Section: Discussionmentioning
confidence: 90%
“…For moderate-severe patients, both monotherapy (intranasal corticosteroid spray; INCS) and combination therapy with antileukotrienes, antihistamines, INCS were preferred. The choice of these therapeutic regimes was primarily attributed to efficacy and cost-effectiveness [ 11 ]. In contrast, the Current Allergic Rhinitis Experiences Survey (CARES) [ 16 ], which assessed the AR management practices followed by the primary healthcare professionals (HCPs) in the U.S., demonstrated that more than 80% of the HCPs stated intranasal corticosteroids as the gold standard for the treatment of AR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Readers of this journal will find the original articles on the treatment adherence and quality of life among adults with chronic urticaria in Singapore [ 3 ], and the attitudes, practices on allergic rhinitis of generalists and specialists in Philippine National Capital Region [ 4 ]. The readers will also find the first study on the pattern of anaphylaxis in Saudi Arabia [ 5 ] and the interleukin-10 and interleukin-5 balance in patients with active asthma, those in remission, and healthy controls from Japan, which showed a similar result from a murine asthma model of immunotherapy [ 6 ].…”
mentioning
confidence: 99%